Unraveling public support for casino gaming: The case of a casino referendum in Penghu. Issue 3 (24th March 2017) - Wu, Jeanette Mei-lan; Tsai, Henry; Lee, Jin-Soo
ABSTRACT: By integrating the social exchange theory (SET) and the theory of planned behavior (TPB), this study unravels the factors associated with residents' intention to support casino gaming development in Penghu in future referenda. Residents' attitudes toward casino gaming development in their community were examined in the SET framework while their intention to support such development was investigated in the TPB framework. Despite that partisan difference did not have a significant interaction with TPB variables, past behavior exerted moderating effects determining residents' intention to support casino gaming development through two TPB variables: subjective norm and perceived behavioral control. Implications are provided. Abbreviations : ATTU: attitude; DPP: Democratic Progress Party; ECOI: perceived economic impact; ENVI: perceived environmental impact; INT: intention to support casino gaming development in future referenda; KMT: Kuomingtang; PBC: perceived behavioral control; PPB: perceived personal benefit; SET: social exchange theory; SN: subjective norms; SOCI: perceived social impact; TPB: theory of planned behavior